The “Manueline” Secular Architecture in Portugal: A Distinctive Style in Lisbon in the Context of Italian Tradition - Smagol, Oxana S. (Actual Problems of Theory and History of Art, 2019)
The Renaissance epoch in Portugal is commonly delineated chronologically as a period between the end of the 15th and the beginning of the 16th centuries. Historically it’s associated with a king Manuel I’s reign (1495–1521), and stylistically it’s known as the “Manueline” style, a capricious, whimsical national style, mingling together contrasting elements: a gothic one, Spanish “plateresque”, king Manuel symbols,encompassing heraldic as well as exotic ones, forged on the way of geographical discoveries and rushes to new horizons. And last but not least, a Renaissance element, North Italian and tramontane. Italian artists in Portugal played their crucial role (Andrea Sansovino), as well as local patrons, inspired by Italian experience when abroad (Alfonso Albuquerque); and those supervising local works, constantly in contact with Italians in Lisbon, a rapidly developing “new center of the world” (Antinio Carneiro). Along with exuberant monastic architecture (Hieronymites monastery in Belém, Pena monastery inSintra, convent of Christ in Tomar), the “Manueline” epoch dawn paved the way for a new urban developmentin general, and palaces’ construction and reorganization, in particular. Unfortunately, a series of earthquakes (16th–18th centuries) resulted in a global demolition of local Renaissance monuments and documents.On one hand, T. Kaptereva scientific contribution to a study of Renaissance Portugal should be noted. On the other, modern European (K. Lawe, L. Fernández-González, A. Jordan Gschwend) new reconstructions and research of Renaissance architecture in the region rests on recent artistic discoveries. They provide a new chance of the “Manueline” style architecture understanding.Here the first problem is to shape a kind of reconstruction and description of Renaissance Lisbon urban ensembles (as Rua Nova), royal residences (Santos, Royal palace on the Tagus river bank, palace of Sintra), private and public buildings (casa dos Bicos), basing on miniatures, maps and paintings. The second task is to interpret (in cases possible) the above said monuments in the context of North Italian Renaissance architectural tradition (facades, porticoes, courts, vaults). Thirdly, the secular architecture in question is analyzed as linked to national identity and strengthening central power in Portugal of Manuel I.
Keywords: Portugal; Lisbon; the Manueline style architecture; Northern Italy